Analisis Studi Kelayakan UMKM Mie Ujang Ditinjau Dari Aspek Pemasaran dan Profit Margin - Andini Aulia Destari; Aprilia Lulu’ul Ma’nunah; Bekti Govinda; Indri Kusuma Dewi; Karunia Novita Febryana; Sintia Rhamadaniah (Jurnal Kewirausahaan Cerdas dan Digital, 2024)
Food production must meet needs that continue to increase along with population growth. One of the noodle processing food production places in Jember Regency is Mie Ujang. This industrial product was successfully marketed as many as 524 bags (13,350 kilograms) in 2018. This research aims to determine effective plans and implementation to increase creativity and innovation in business feasibility to compete with competitors. This research uses qualitative methods with data collection techniques, namely interviews and documentation. Data sources include primary data and secondary data. This research shows that Mie Ujang is very suitable for continuing to carry out its business processes because it has an average production volume of 24 bags or around 600 kg per day. Mie Ujang should improve its marketing so that its market reach is wider.